Wind Instrumentalists and Temporomandibular Disorder: From Diagnosis to Treatment - Miguel Pais Clemente; Joaquim Mendes; André Moreira; Ricardo Vardasca; Afonso Pinhão Ferreira; José Manuel Amarante (MDPI AG, 2018)
Introduction: Temporomandibular disorders (TMD) involve the presence of pain or dysfunction on certain areas of the Cranio-Cervico-Mandibular Complex (CCMC), such as the masticatory muscles, the temporomandibular joint (TMJ) and associated structures like the postural muscles of the cervical region, can be considered as a sub-group of musculoskeletal disorders. Wind instrument players, as a consequence of their musical performance and its relation with the CCMC, can develop a TMD associated to muscle hyperactivity of certain elevator muscles, or even an increase of the intra-articular pressure in the functioning of the TMJ throughout musical activity. Aim: The objective of this paper is to describe the necessary and elementary steps in the diagnoses and treatment of a wind instrumentalist with a temporomandibular disorder, with the introduction of infrared thermography during this procedure. This case study also has the purpose of presenting the usefulness of piezoresistive sensors in the analysis of the clarinettists’ embouchure. Methodology: A Caucasian, 30-year-old female clarinettist was assessed through a clinical examination following the Diagnostic Criteria for TMD (RDC/TMD), as a complementary tool of diagnosis, a thermal imaging infrared camera, Flir E60 (Wilsonville, OR, USA), was used in order to analyse the above referred articular and muscular regions. The complementary examination protocol implemented with this clarinet player also involved the analyses of the embouchure with the support of piezoresistive sensors. Results: The clinical outcomes resulting from this work were based on the RDC/TMD diagnoses indicated that the clarinet player had an internal derangement on both TMJ, with an osteoarthritis on the left TMJ and an anterior disc displacement with reduction on the right TMJ. The infrared thermograms that were analysed, verified the existence of a temperature differential of the anterior temporal muscle (0.1 °C), the TMJ (0.1 °C) and the masseter muscle (0.7 °C), and after the occlusal splint therapy the asymmetry related to the master muscle reduced to 0.3 °C. The high pitches can reach values of 379 g of force induced to the tooth 21 comparing to the 88 g of force applied on tooth 11. The embouchure force measurements consistently presented greater forces during the higher notes, followed by the medium notes and finally the low notes and this happened with higher pressures being transmitted always to tooth 21. Conclusion: Performing arts medicine should understand the major importance of the dentistry field in the daily life of a professional musician, and the significance of implementing routine screening procedures of dental examinations, with infrared thermograms examination of distinct areas of the CCMC, as well as the use of sensors on the analyses of an eventual asymmetrical embouchure. Employing these techniques in dentistry will create the chance of preventing the overuse of some anatomical structures, with an early diagnosis and the correct monitoring of these areas.